Kepatuhan Penatalaksanaan Diabetes Mellitus Terhadap Kadar Gula Darah Pasien Diabetes Mellitus Tipe II - Soenarto Juliana (Jurnal Keperawatan Notokusumo, 2013)
Background: Diabetes Mellitus (DM) is a trouble of metabolism chronic marked by the existence of increase of rate blood sugar. Prevalence of DM in region work the Puskesmas Banguntapan I Bantul in Januari-Juli 2010 patient of DM type II noted by 199 people. Mostly them less knowing about of DM disease. An effort to avoid an increase or decrease in blood sugar levels of diabetic patients will require the active participation of patients, families and health professionals. Good management of DM will control the sugar levels of patients so that patients will be able to live longer with excellent quality. Objective : To know the relation of compliance of management DM (order compliance the eat/diet, athletic regularly, take medicine, following counselling about management of DM type II) with the rate of blood sugar at patient of DM Type II in region work the Puskesmas Banguntapan I Bantul. Method : Quantitative descriptive research correlation with the approach of cross sectional. This research is conducted in Puskesmas Banguntapan I Bantul with the population all DM patient which take care of the street 199 people. Sampel in this research amount to 67 people with the intake sampel by purposive sample. Method of data collecting by questionnaire and analyse the data with the analysis of univariate and bivariate. Result: Patient compliance about management DM of most is not obedient (52,2%). As for at all of compliance of management DM of most at every phase of DDM execution also show is not obedient, for example phase of food diet (49,3%), corporeal practice (67,2%), medication (44,8%), counselling (70,1%) and monitoring of rate of blood sugar (49,3%). While rate of blood sugar at patient of DM Type II most (62,7%) included in ugly criterion in control (? 200 mg / dL). Result of correlation test show there are relation which signifikan of between compliance of management DM with the rate of blood sugar at patient of DM Type II with the correlation coefficient 0,611 and probability 0,000 at level signifikansi 5%.